Brokered Pathways to Justice and Cracks in the Law: A Closer Look at the Claims‐Making Experiences of Low‐Wage Workers. Issue 1 (March 2015) - Gleeson, Shannon
Abstract : This article examines the factors that shape low‐wage workers' decision to mobilize their legal rights following a workplace violation. I discuss the diverse mechanisms of employer retaliation, including the role of employer sanctions, the role of community social networks, and the myriad challenges that claimants face in navigating the labor standards enforcement bureaucracy. I demonstrate how, although unauthorized status is formally not a barrier for accessing many key benefits in California, the structural position of unauthorized workers place them at a particular disadvantage, significantly so for subcontracted and seasonal workers. These data are based on a of survey of 453 claimants who have sought assistance from a nonprofit legal aid clinic for low‐wage workers in the San Francisco Bay Area, and in‐depth follow‐up interviews with a representative subsample of 90 respondents, 12–30 months later. Five years of participant observation at a legal aid clinic focused on workers' compensation claims, and interviews with 24 injured workers, also inform these findings.